The effect of micronutrient on thyroid cancer risk: a Mendelian randomization study - Shen, Jiali; Zhang, Hong; Jiang, Hongzhan; Lin, Huihui; He, Jiaxi; Fan, Siyue; Yu, Doudou; Yang, Liping; Tang, Hui; Lin, Ende; Li, Lianghui; Chen, Lijuan (Frontiers in Nutrition, 2024)
Background The effect of micronutrients on thyroid cancer has been studied in observational studies, however, the cause of relationships has not yet been determined. Thyroid cancer was the subject of a Mendelian randomization (MR) analysis of micronutrients. Aimed to determine whether micronutrient intake has a causal impact on the chance of developing thyroid cancer. Methods We used a Mendelian randomization (MR) analysis with two samples. Our circulation levels of Cu, Ir, Zn, Ca, VD, and VC were reflected by genetic variations reported from GWAS in individuals of European ancestry. For the GWAS outcome of thyroid cancer. Sensitivity studies that included MR-Egger, weighted median/mode tests, and a more open selection of variations at a genome-wide sub-significant threshold were added to our inverse-variance weighted (IVW) MR study. Results Using the IVW approach, we did not find evidence that any of the micronutrients to thyroid cancer (Cu: odds ratio [OR = 0.88, p = 0.41]; Zn: odds ratio [OR = 0.87, p = 0.40]; Ir: odds ratio [OR = 1.18, p = 0.39]; Ca: odds ratio [OR = 1.12, p = 0.43]; VC: odds ratio [OR = 0.95, p = 0.22]; VD: odds ratio [OR = 0.89, p = 0.04]). The heterogeneity (p > 0.05) and pleiotropy (p > 0.05) testing provided confirmatory evidence for the validity of our MR estimates. Conclusion This study does not provide evidence that supplementation with micronutrients including Cu, Ir, Zn, Ca, VD, and VC can prevent thyroid cancer.